PENGARUH KINERJA CSR DAN BOARD SIZE TERHADAP KINERJA PERUSAHAAN - Delima; Usman, Berto (FEB Universitas Sam Ratulangi Manado, 2024)
Based on agency and stakeholder theories, this study will investigate how CSR performance and board size affect firm performance. The market measurements used are stock returns and stock trading volume of banking companies incorporated in the IDX. Operationally, this study uses a sample of 32 banking companies listed on the Indonesia Stock Exchange from 2018 to 2022 to see if company performance is affected by CSR performance and board size. Based on the characteristics and structure of panel data, this study uses a panel regression analysis of 160 observations (company-years). In addition, the common-effects model (CEM) is also used for the analysis. The results show that CSR performance and board size do not affect firm performance, measured by stock returns. The CSR performance variable has no influence on firm performance as measured by trading volume. However, the board size variable in this finding has an effect on firm performance measured using trading volume. This indicates that in the context of this study, these factors are not the main determinants of firm performance based on stock returns and trading volume.